A comparison of the potential role of the tetrodotoxin-insensitive sodium channels, PN3/SNS and NaN/SNS2, in rat models of chronic pain - Porreca, Frank (The National Academy of Sciences, 1999)
Alterations in sodium channel expression and function have been suggested as a key molecular event underlying the abnormal processing of pain after peripheral nerve or tissue injury. Although the relative contribution of individual sodium channel subtypes to this process is unclear, the biophysical properties of the tetrodotoxin-resistant current, mediated, at least in part, by the sodium channel PN3 (SNS), suggests that it may play a specialized, pathophysiological role in the sustained, repetitive firing of the peripheral neuron after injury. Moreover, this hypothesis is supported by evidence demonstrating that selective “knock-down” of PN3 protein in the dorsal root ganglion with specific antisense oligodeoxynucleotides prevents hyperalgesia and allodynia caused by either chronic nerve or tissue injury. In contrast, knock-down of NaN/SNS2 protein, a sodium channel that may be a second possible candidate for the tetrodotoxin-resistant current, appears to have no effect on nerve injury-induced behavioral responses. These data suggest that relief from chronic inflammatory or neuropathic pain might be achieved by selective blockade or inhibition of PN3 expression. In light of the restricted distribution of PN3 to sensory neurons, such an approach might offer effective pain relief without a significant side-effect liability.